Arts in transformative learning: an arts-based duoethnography. Issue 5 (3rd September 2019) - Chien, Ting Fang; Yang, Hsiu-Chun
ABSTRACT: In this research, two art educators discuss their understanding and applications of transformative learning theory (TL) and the Reggio Emilia approach (REA) as art practitioners by exchanging arts-based letters, which they see as a type of duoethnographic method for qualitative research. They share a teaching philosophy that stresses art as a transformative tool for learning through verbal and written dialogues, despite teaching different age groups of students. One is an art instructor in higher education; the other is an early childhood art teacher. The two art educators believe that art significantly transforms their teaching practices and their students' learning. In the process of sharing the arts-based letters, they learn TL and REA from each other's perspectives. They anticipate that their reflexive research can provide educators and qualitative researchers a different lens to reflect through which to view teaching and learning.